Tabel Kehidupan Daphnia pulex Setelah Aplikasi Pupuk Organik = Life Table of Daphnia pulex After Organic Fertilizer Application - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian dan Pangabdian kepada Masyarakat, Universitas Gadjah Mada, 1999)
ABSTRACT Daphnia pulex is one of zooplankton species which has been used frequently in fish larvae rearing as a natural food, because it can be cultured easily, has high reproductive potential, and contain high nutrition value as well. To increase its population growth rate organic fertilizer is necessary. However, the best introducing time of Daphnia pulex into culture system after organic fertilizer application is not known yet. The purpose of this experiment was to assess the best time to introduce Daphnia pulex into the culture system after organic fertilizer application. Neonates of Daphnia pulex were individually dispenses into culture tubes (erlenmeyer 50 mL) suspended in aquarium (60 litre). Each culture tubes (contain 10 neonates 0 day old) tied by plankton net 75 mm mesh size around the mouth. Four treatments representing different days (0, 5, 10, and 15 days) after organic fertilizer (cattle manure, poultry droppings, dried rice stalks, stem of banana, 1 :1 :1 :1, at the rate of 0.263 kg.m.5) application and control (without organic fertilizer) in four replications were tested. Daphnia pulex population in the culture tubes were examined daily to construct life table. Water quality parameters measured were temperature, dissolved oxygen, pH, NH3-N, NO3-N, PO4-P, and turbidity. Application of organic fertilizer into culture media of Daphnia pulex resulted in increasing survival rate, intrinsic rate of natural increase (r), net reproductive rate (R), and decrease average generation time (T) significantly than that of control, but not to time to first reproduction (A), peak reproduction (I), and life span (W). Among the time after organic fertilizer application treatment, except 0 day, there were no significant differences. All Daphnia pulex population dynamic parameters in 0 day after application treatment showed low response compared to 5 days after application because of water quality (ammonia, DO, and pH) deterioration. The best time to introduce Daphnia pulex after organic fertilizer application was 5 day.